Avaliação da cefaleia e qualidade de vida em mulheres vítimas de escalpamento na Amazônia - (:unkn) unknown (Brasil)
Background: Scalping is an accident caused by the abrupt avulsion of the scalp on the motor shaft of small vessels, causing physical and psychosocial disorders. The after affects in the victims become permanent and can affect the quality of life and, among them, the headache. Objective: To evaluate the impact of headache on the quality of life of female victims of scalping. Methods: Descriptive, transversal and quantitative study approved by the Ethics and Research Committee of the Federal University of Amapa. Thirty-seven women, totally or partially scalped, were registered in the Public Defender's Office of the State of Amapá and had headache. The socio-demographic identification form, the international classification of headache symptom diagnosis manual and the WHOQOL-bref quality of life questionnaire were used as instruments of the research. For statistical analysis, the Statistical Package for the Social Sciences (SPSS) was used with the tests: Shapiro-Wilk, Mann Whitney and Kruskal-Wallis test in addition to Sperman's correlation. P <0.05 was considered as significance. RESULTS: The sample included 37 women aged 18-71 years. Of these, 64.9% presented headache as the main symptom; 35.1% classified the pain as pulsatile and 29.7% throughout the head; 56.8% say they came after an accident. From the diagnosis, 37.8% had migraine associated with trauma, 29.7%. In relation to quality of life, the most affected domains were the environment and the general perception of health. Conclusion: Headache is a prevalent symptom in the victims of scalping and is related to interference in a good quality of life
Keywords: Escalpelamento; Cefaleia; Qualidade de vida; CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; PROCEDIMENTOS E ATENÇÃO EM SAÚDE NO TRÓPICO ÚMIDO DA AMAZÔNIA; EPIDEMIOLOGIA E SAÚDE PÚBLICA